Actualidad de la teoría de la enajenación. Sol Arguedas. - Arguedas, Sol (Méx., D.F : UNAM, 1994)
Síntesis de las ideas de Marx sobre la alienación
Keywords: MARX, KARL -- 1818-1883; ALIENACIÓN; TRABAJO